How a roket works - Bryan, Lara; Attia, Caroline; Ryder, Caroline (London Usborne, 2022)
It's time for take off! peep inside a rocket to find out how it works, and join the astronauts on an exciting adventure up into space
Scientific notions
Keywords: Science